2017
DOI: 10.1073/pnas.1708044114
|View full text |Cite
|
Sign up to set email alerts
|

5-hydroxymethylcytosine accumulation in postmitotic neurons results in functional demethylation of expressed genes

Abstract: 5-hydroxymethylcytosine (5hmC) occurs at maximal levels in postmitotic neurons, where its accumulation is cell-specific and correlated with gene expression. Here we demonstrate that the distribution of 5hmC in CG and non-CG dinucleotides is distinct and that it reflects the binding specificity and genome occupancy of methylcytosine binding protein 2 (MeCP2). In expressed gene bodies, accumulation of 5hmCG acts in opposition to 5mCG, resulting in “functional” demethylation and diminished MeCP2 binding, thus fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
149
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(164 citation statements)
references
References 52 publications
15
149
0
Order By: Relevance
“…Taken together, these data suggest that MeCP2 behavior in live neurons is tightly regulated by epigenetic modifications of the DNA. Thus, as predicted from previous biochemical studies Mellen et al, 2017), a decrease in the level of DNA methylation as a result of Dnmt3a deletion causes a reduction in the fraction of stably bound MeCP2 in vivo. Conversely an increase in DNA methylation as a consequence of deletion of the Tet oxidases results in an increase in the fraction of stably bound MeCP2.…”
Section: Mecp2 Chromatin Binding Is Sensitive To Dna Modification Levsupporting
confidence: 76%
See 2 more Smart Citations
“…Taken together, these data suggest that MeCP2 behavior in live neurons is tightly regulated by epigenetic modifications of the DNA. Thus, as predicted from previous biochemical studies Mellen et al, 2017), a decrease in the level of DNA methylation as a result of Dnmt3a deletion causes a reduction in the fraction of stably bound MeCP2 in vivo. Conversely an increase in DNA methylation as a consequence of deletion of the Tet oxidases results in an increase in the fraction of stably bound MeCP2.…”
Section: Mecp2 Chromatin Binding Is Sensitive To Dna Modification Levsupporting
confidence: 76%
“…Biochemical studies have initially determined that the ability of MeCP2 to bind DNA depends on the presence of methylated cytosines (5mC) and more recently, it was shown that hydroxylation of these sites (5hmC), when it occurs in the context of CpG, disrupts this interaction ( Figure 4SA) (Gabel et al, 2015;Mellen et al, 2017). Once neurons become postmitotic, they begin accumulating de novo DNA methylation sites by the activity of DNA methyltransferase 3a (DNMT3a), as well as converting 5mC to 5-hyroxymethylcytosine (5hmC) through the enzymes Tet1, 2 and 3 (Lister et al, 2013;Stroud et al, 2017).…”
Section: Mecp2 Chromatin Binding Is Sensitive To Dna Modification Levmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other tissue types, 5hmC is enriched in the bodies of actively transcribed genes in postmitotic neurons, and accumulates at the flanking region of enhancers and TF binding sites [15,85,86]. In addition, 5hmC was found to accumulate in adult neurons as synaptogenesis occurs, although its content and distribution varies among different kind of neurons [20].…”
Section: Ectodermmentioning
confidence: 84%
“…Indeed, it was recently shown that distribution of 5hmC in CG and non-CpG dinucleotides is distinct and reflects the binding specificity and genome occupancy of MeCP2 [86]. In addition, loss of MeCP2 led to specific reduction of 5hmC signals in dynamically hydroxymethylated intragenic non-CpGs involved in gene activation [20].…”
Section: Ectodermmentioning
confidence: 99%